Kitolod (Isotoma longiflora Presi) Leaf Extract as a Bioreductor in Silver Nanoparticle Synthesis - Alifiani Maulida; Gusrizal Gusrizal; Anis Shofiyani (UNIVERSITAS SEBELAS MARET (UNS), 2026)
Silver nanoparticles (AgNPs) were synthesized using kitolod (Isotoma longiflora Presi) leaf extract as a bioreductor. This research aims to investigate the ability of extracts to act as reducing agents in the formation of AgNPs and to characterize the resulting AgNPs. The synthesis was carried out under the following conditions: pH of extract 12, reaction time 90 minutes, silver nitrate concentration 2 × 10-4 M, and extract concentration 0.08%. Fourier transform infrared (FTIR) spectra confirmed the involvement of phytochemicals in the reduction of Ag+ to Ag0. The synthesized AgNPs were spherical, with an absorption peak at around 420 nm, an average particle size of 67.38 nm, a zeta potential of -23.6 mV, and a polydispersity index (PDI) of 0.697. Stability testing showed that the synthesized AgNPs remained stable for two months at room temperature.